La gripe en adultos en américa latina, situación actual y tendencias futuras: Una declaración de consenso - Bonvehí, Pablo E.; Istúriz, Raúl E.; Labarca, Jaime A.; Rüttimann, Ricardo W.; Vidal, Edison Iglesias de Oliveira [UNESP]; Vilar-Compte, Diana (My University, 2012)
In Latin America, adult influenza is a serious disease that exacts a heavy burden in terms of morbidity, mortality, and cost. Although much has been written about the disease itself, relatively little information has been compiled on what could be done to reduce its impact across the region, particularly from the perspective of clinicians with firsthand experience in confronting its effects. To fill this data gap, in 2011, the Pan American Health and Education Foundation (PAHEF) and the U.S.-based nonprofit Fighting Infectious Diseases in Emerging Countries (FIDEC) organized a conference and convened a panel of Latin American scientistclinicians with experience and expertise in adult influenza in the region to 1) discuss the major issues related to the disease and 2) develop and produce a consensus statement summarizing its impact as well as current efforts to diagnose, prevent, and treat it. The consensus panel concluded a more concerted and better-coordinated effort was needed to reduce the adverse impact of seasonal influenza and future pandemics, including more surveillance, more active involvement by both governmental and nongovernmental organizations, and a much greater effort to vaccinate more adults, especially those at high risk of contracting the disease. In addition, a new approach for diagnosing influenza was recommended.
Influenza among adults in Latin America, current status, and future directions: a consensus statement
Keywords: Adult; Consensus development conferences as topic; Human; Immunization; Influenza; Influenza vaccines; Latin America; disease prevalence; health risk; immunization; infectious disease; influenza; morbidity; mortality